A differential game model of incentive-based student recruitment, retention and faculty engagement in higher education. (1st January 2013) - Leonce, Tesa E.
Many public and private four-year colleges and universities are facing the issue of declining enrolment. Several universities adopt a centralised approach to recruiting, where efforts are concentrated in the admissions function of the academic institution. These recruitment methods mirror a 'catch all' approach for prospective students across all academic disciplines. The concern with this centralised recruitment method is the level of detachment from key success/retention criteria that is unique to different academic disciplines. This study seeks to determine whether significant correlation exists between student recruitment methods and retention statistics among for-profit universities and to examine the efficacy of a more decentralised approach to recruiting students, much like the model adopted among athletic institutions. Overall, we find that actively engaging faculty scouts in recruitment and retention efforts via a revenue-sharing programme can be effective if: 1) achieving a progressively larger incoming students pool is a shared goal; 2) reaching enrolment sustainability is a priority, where marginal net growth of the stock is positive; 3) the bulk of the institutional revenues come from tuition fees, relative to independent outside sources; 4) the revenue share awarded to faculty scouts is perceived by them as competitive.